(untitled) (Annals of Medical Research, 2022)
Aim: Aortic stiffness is an important risk factor that reflects the mechanical tension and elasticity of the aorta and predicts cardiovascular mortality and morbidity. However, it has been found that aortic stiffness contributes to both symptom burden and clinical outcomes in patients with aortic stenosis (AS). In our study, we aimed to evaluate the effect of transcatheter aortic valve implantation (TAVI) on aortic elasticity parameters by echocardiography in patients with severe aortic stenosis, especially with preserved ejection fraction. Materials and Methods: A total of 55 consecutive patients with symptomatic severe AS who underwent TAVI were included in the study. Demographic data, echocardiographic and aortic elasticity measurements of all patients were measured before and 6 months after the procedure. To evaluate the elastic properties of the aorta, aortic strain, distensibility and stiffness index were calculated. Results: Left ventricular mass index (LVMI) (p <0.001) and aortic stiffness (p <0.001) were decreased, while aortic strain (p <0.001) and aortic distensibility (p <0.001) were found to be increased in the measurements performed at 6 months after TAVI. In the regression analysis, age and LVMI were found to be independent predictors for predicting improvement in aortic stiffness; on the other hand, LVMI also independently predicted the increase in aortic distensibility. Conclusion: Improvement in aortic elastic properties and left ventricular functions were found in patients who underwent TAVI. Age and LVMI were observed to predict the improvement in stiffness and distensibility of the aorta in patients undergoing TAVI, especially in AS patients with preserved ejection fraction.